Effect Of The Addition Of Guar Gum And Red Palm Oil On The Physical And Chemical Of Mellorine Sari Tempeh - Erza Alfida Martha; Jariyah Jariyah; Rosida Rosida (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
The study aimed to determine the effect of the addition of guar gum and red palm oil on the physicochemical characteristics of mellorine sari tempeh and obtain the best combination on mellorine.The study used a Complete Randomized Design (RAL) two-factor pattern with three repetitions.Factor I is the addition of guar gum (v/v) 0.4%;0.6%; and 0.8%. Factor II is the addition of red palm oil 3%, 6%, and 9%. The results of this study showed that mellorine sari tempeh has met SNI ice cream standards and meets european patent specification of mellorine standards .The best treatment obtained from the addition of guar gum 0.8% and red palm oil 9% produces mellorine with protein content of 4.024%, fat content of 6,317%, overrun 18,03%, melting time of 23,53 minutes, antioxidant capacity of 7,121%, total solids of 39,06%, emulsion stability 95,86%, viscocity of 2123mPa.s and Vitamin A of 2,89mg/100gr.